Income Dynamics and Risk of Colorectal Cancer in Individuals With Type 2 Diabetes: A Nationwide Population-based Cohort Study - Yong-Moon Mark Park; Benjamin C. Amick III; Pearl A. McElfish; Clare C. Brown; Mario Schootman; Marie-Rachelle Narcisse; Seong-Su Lee; Yoon Jin Choi; Kyungdo Han (Journal of Epidemiology)
Background: Individuals with type 2 diabetes mellitus (T2DM) have increased colorectal cancer (CRC) risk, but it is unknown whether income dynamics are associated with CRC risk in these individuals. We examined whether persistent low- or high-income and income changes are associated with CRC risk in non-elderly adults with T2DM. Methods: Using nationally representative data from the Korean Health Insurance Service database, 1,909,492 adults aged 30 to 64 years with T2DM and no history of cancer were included between 2009 and 2012 (median follow-up of 7.8 years). We determined income levels based on health insurance premiums and assessed annual income quartiles for the baseline year and the four preceding years. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated after adjusting for sociodemographic factors, CRC risk factors, and diabetes duration and treatment. Results: Persistent low income (ie, lowest income quartile) was associated with increased CRC risk (HR5 years vs 0 years 1.11; 95% CI, 1.04–1.18; P for trend = 0.004). Income declines (ie, a decrease ≥25% in income quantile) were also associated with increased CRC risk (HR≥2 vs 0 declines 1.10; 95% CI, 1.05–1.16; P for trend = 0.001). In contrast, persistent high income (ie, highest income quartile) was associated with decreased CRC risk (HR5 years vs 0 years 0.81; 95% CI, 0.73–0.89; P for trend < 0.0001), which was more pronounced for rectal cancer (HR 0.64; 95% CI, 0.53–0.78) and distal colon cancer (HR 0.70; 95% CI, 0.57–0.86). Conclusion: Our findings underscore the need for increased public policy awareness of the association between income dynamics and CRC risk in adults with T2DM.